Ethnomathematics exploration of Kaneka and Mariam tradional games in Nangapanda, Nusa Tenggara Timur culture - Amsikan, Stanislaus; Deda, Yohanis Ndapa (Journal of Honai Math, 2023)
This research explores the mathematical concepts and cultural values in Kaneka (marbles) and Mariam (Patok Lele) traditional game. The type of research used is ethnographic research with a qualitative approach. The research instruments used consisted of main instruments and auxiliary instruments. The research location was Nangapanda sub district, with the research subject being a 58 years old traditional leader and 10 years old traditional game player. Data collection techniques in this study used technical triangulation by observing, interviewing and documenting the same sources. The data analysis technique used in this study refers to the Spradley design, namely domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. The results showed that first, the Kaneka traditional game contains the elements of ball and half ball shapes, distance, and counting points, including addition operations, and second, the Mariam traditional game contains the elements of cylinder shapes, comparison, direction, and calculating score including addition and multiplication operations